Modeling Price Policy of Industries within the Frames of Inter-Sectoral Balance Methodology - N. A. Moiseev; I. A. Vnukov (Вестник Российского экономического университета имени Г. В. Плеханова)
The subject of inter-sectoral balance has been adequately developed in scientific community, however, we think that insufficient attention was paid to inserting price rates of industries in the model of inter-sectoral relations, as they produce a serious impact on making decisions concerning each industry production. The article deals with working-out a mathematic approach to modeling industry behavior in view of price policy development. The theoretical base of the research was formed by key provisions of the economic theory and the theory of inter-sectoral balance. The authors analyze dynamics of product prices set by industries with regard to inter-sectoral dependence and respective changes in output, added value, margin and volumes of sold products in each industry. As a result of the research the inter-sectoral model of shaping price policy of industries was built, which takes into account parameters of demand and urge of every industry for maximum profits. Different scenarios of changing demand parameters and production interactions were studied. Model experiments allowed authors to come to the conclusion that a rise in demand for one industry product cannot always increase production of related industries. As product price in the industry goes up, costs of other industries also rise, which can have an adverse effect on their product demand on the part of end customer. And on the contrary, a drop in demand for one industry product can support other related industries on constant demand factors at the expense of cost cutting. The proposed model could be useful for private and state sectors in planning investment policy at the same time it could reveal macro-economic trends, which is necessary to resolve problems of tardy or inadequate response of business entity on possible risks.